Simultaneous oral, bone, and lung manifestations of tuberculosis - Pinto, Antonione Santos Bezerra; Furuse, Cristiane; Soares, Haroldo Arid; Thomaz, Luiz Alexandre; Teixeira, Lucas Novaes (Journal of Oral Diagnosis, 2017)
Tuberculosis (TB) is a chronic granulomatous disease caused by Mycobacterium tubercu- losis, which is transmitted by saliva droplets from patients with active pulmonary disease to persons in close contact with those infected. TB remains a leading cause of morbidity and mortality in developing countries, including Brazil. This disease primarily occurs in the lungs; however, other organs can be affected. Cervical tuberculous lymphadenitis or scrofula is the commonest form of extrapulmonary TB, particularly in immunocompro- mised patients. In the stomatognathic system, the tongue is the site most often affected by TB, whereas bone is rarely affected. The diagnosis of the active form of TB is made based mainly on clinical and radiographic findings, histopathologic features and sputum culture for M. tuberculosis, while the latent form of TB can be detected by tuberculin skin test or an interferon-γ release assay. The present article aimed to report a case of TB occurring concurrently in the oral cavity, bone and lungs.